Design thinking for cyber deception - Ashenden, Debi; Black, Rob; Reid, Iain D.; Henderson, Simon (The University of Hawaiʻi at Mānoa, 2021)
Cyber deception tools are increasingly sophisticated but rely on a limited set of deception techniques. In current deployments of cyber deception, the network infrastructure between the defender and attacker comprises the defence/attack surface. For cyber deception tools and techniques to evolve further they must address the wider attack surface; from the network through to the physical and cognitive space. One way of achieving this is by fusing deception techniques from the physical and cognitive space with the technology development process. In this paper we trial design thinking as a way of delivering this fused approach. We detail the results from a design thinking workshop conducted using deception experts from different fields. The workshop outputs include a critical analysis of design provocations for cyber deception and a journey map detailing considerations for operationalising cyber deception scenarios that fuse deception techniques from other contexts. We conclude with recommendations for future research.
Keywords: Cyber Deception and Cyber Psychology for Defense; behaviour; cyber deception; decision making; design thinking; innovation